Pengaruh Kepemimpinan Kepala Sekolah, Motivasi Kerja, Lingkungan Kerja dan Kepuasan Kerja Terhadap Kinerja Guru SMP N 3 Lasem - Nadya Sivana Mulia; Ming Ming Lukiarti (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2026)
The purpose of this study is to prove the influence of principal leadership, work motivation, work environment and job satisfaction on the performance of teachers of SMP N 3 Lasem. The data collection technique in this study used a questionnaire. The data source used in this study is from primary data sources in the form of respondents' answers from the distribution of questionnaires to teachers of SMP N 3 Lasem. The population in this study is all teachers of SMP N 3 Lasem. The sampling method used in this study is using saturated samples, so the sample in this study is all 33 teachers of SMP N 3 Lasem. The data analysis technique used is multiple linear regression. The results of the study indicate that the job satisfaction variable has a significant positive effect on the performance of teachers at SMP N 3 Lasem, while the variables of principal leadership, work motivation and work environment have a positive but insignificant effect on the performance of teachers at SMP N 3 Lasem, while the results of the determination coefficient test show that the Adjusted R Square value is 0.865 so that it can be interpreted that the variables of principal leadership, work motivation, work environment and job satisfaction can explain 86.5% of teacher performance, while the remaining 13.5% of teacher performance is influenced or explained outside this research model.